How Do Controls Impact Employee Trust in the Employer?. Issue 3 (28th April 2015) - Weibel, Antoinette; Den Hartog, Deanne N.; Gillespie, Nicole; Searle, Rosalind; Six, Frédérique; Skinner, Denise
Abstract : Do organizational controls facilitate or hinder employees' trust in their organization? We addressed this question through a mixed‐methods design using three studies. Based on a literature review and an open‐response survey study (Study 1), we developed a theoretical model proposing that organizational control is positively related to employees' trust in their organization, and that this relationship is mediated by procedural fairness and organizational prestige. This mediated model was tested and supported in a quantitative survey of 582 European managers and professional employees from a range of organizations (Study 2). A complementary, qualitative interview‐based study (Study 3) confirmed that well‐implemented controls facilitate trust in the organization; however, poorly implemented control systems that are inconsistent, overly rigid, or incentivize untrustworthy behavior can undermine trust in the organization. © 2015 Wiley Periodicals, Inc.